Structure variety and its potential effects on biological activity of tea polysaccharides - Ting Hu; Peng Wu; Jianfeng Zhan; Weixin Wang; Junfeng Shen; Meiyan Wang; Chi-Tang Ho; Shiming Li (Food Science and Human Wellness)
Tea polysaccharides (TPSs), one of the major bioactive ingredients in tea, have been widely studied due to their variety of biological activities, including antioxidant, cancer prevention, hypoglycemia, anti-fatigue, anti-coagulant, anti-obesity and immunomodulatory effect. The biological effectiveness of TPSs has direct relation with their structures such as monosaccharide composition, molecular weight, glycosidic linkages, conformation and others, which can be influenced by tea materials, processing methods, extraction and purification procedures among others. Comparing to the study of tea polyphenols, the exploration of TPSs in structural elucidation and biofunctionality is very preliminary. Yet several factors affecting the structural change of TPSs have been studied and identified. Consequently, the variation of some TPS biological activity brought by the change of TPS structures has been evaluated and preliminary correlation of structure activity relationship of TPSs has been performed. Therefore, this review aims to serve as a summary research report regarding the influencing factors on TPSs structures and consequential effects on the biological activities of TPSs. We hope to provide updated information and systematic references for future study and functional food development of TPSs.